Influence of spectrum loading sequences on fatigue life in a high-temperature environment - Zakaria, Kamarul Ariffin (Elsevier, 2013)
This paper discusses the fatigue life behaviour of aluminium alloy AA6061-T6 under spectrum loadings. Load sequences in spectrum loadings can have significant effects on fatigue life at room temperature and within the elevated temperature range. The main objective of this paper is to investigate the influences of load sequences effect on fatigue life at elevated temperature. Fatigue strain signal was obtained from the engine mount bracket of an automobile under normal driving conditions. Constant amplitude loading, high-to-low, and low-to-high loading sequences were then derived from the original fatigue strain signal to observe the fatigue behaviour at both room and elevated temperatures. The fatigue test was performed on AA6061-T6 specimen according to the ASTM E466 standard using a 100 kN servo-hydraulic fatigue testing machine within the temperature range of 27–250 C. The elevated temperature range was chosen based on the maximum temperature of the engine mount bracket and the extreme temperature of the cylinder head that can be reached in service. After the test, fatigue fracture surfaces were sectioned and inspected using a high-magnification microscope. Results show that fatigue life behaviour at room temperature was significantly influenced by the load sequences in spectrum loadings. On the other hand, the effect of load sequences at a higher temperature was reduced.